Inverse analysis methodology on metal sheets for constitutive parameters identification. (1st January 2013) - Prates, P.A.; Fernandes, J.V.; Oliveira, M.C.; Sakharova, N.A.
This work proposes an inverse analysis methodology for determining the constitutive models parameters, used to describe the plastic behaviour of metal sheets, from results of a single experimental biaxial tensile test on a flat cruciform sample. The proposed methodology is based on a direct analysis of finite element simulation results carried out for different combinations of material plastic properties. The biaxial test sensitivity to the in-plane r -value distribution was evaluated. An inverse analysis methodology was thus established, enabling the determination of the yield criterion parameters by evaluating the relative error between numerical and experimental results of the biaxial tensile test, namely the load evolution with the displacement and the equivalent strain distribution along the symmetry axes. Finally, the proposed methodology was numerically validated throughout the identification of Hill'48 yield criterion parameters for a material with a plastic behaviour well described by this criterion and the Swift hardening law.